2015
DOI: 10.1111/cen.12874
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of gonadal dysfunction are more predictive of hypopituitarism than nonspecific symptoms in screening for pituitary dysfunction following moderate or severe traumatic brain injury

Abstract: Symptoms of hypogonadism are sufficiently predictive of hypopituitarism to justify screening for hypopituitarism after moderate/severe TBI. Nonspecific symptoms of hypopituitarism are no more predictive than unselected screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Prevalence of hypogonadism was estimated at about 1.9% to 17.1% ( Alavi, Tan, Menon, Simpson, & Hutchinson, 2016 ; Schneider, Kreitschmann-Andermahr, Ghigo, Stalla, & Agha, 2007 ; Silva et al, 2015 ). Patients with symptoms of hypogonadism (that included ED) after TBI were even more predictive of hypopituitarism than other symptoms (58% vs 16%, P <.0001) ( Cuesta et al, 2016 ). Medications, such as antiepileptic drugs used to prevent posttraumatic seizure, can also attribute organic ED ( Yang & Wang, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of hypogonadism was estimated at about 1.9% to 17.1% ( Alavi, Tan, Menon, Simpson, & Hutchinson, 2016 ; Schneider, Kreitschmann-Andermahr, Ghigo, Stalla, & Agha, 2007 ; Silva et al, 2015 ). Patients with symptoms of hypogonadism (that included ED) after TBI were even more predictive of hypopituitarism than other symptoms (58% vs 16%, P <.0001) ( Cuesta et al, 2016 ). Medications, such as antiepileptic drugs used to prevent posttraumatic seizure, can also attribute organic ED ( Yang & Wang, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that TBI results in problems and disturbances such as inappropriate sexual behaviors and overall sexual dysfunctions in patients after TBI ( Hanks, Sander, Millis, Hammond, & Maestas, 2013 ; Sander, Maestas, Pappadis, Hammond, & Hanks, 2016 ). Several physical factors such as hypogonadism ( Cuesta et al, 2016 ) and prophylactic antiepileptic drugs ( Yang & Wang, 2016 ) could attribute organic ED, in addition to neuropsychological and neuropsychiatric disorders ( Farre, Fora, & Lasheras, 2004 ; Shamloul & Ghanem, 2013 ; Yafi et al., 2016 ). The association between TBI and ED was not studied specifically.…”
mentioning
confidence: 99%
“…ACTH deficiency in UHB patients was defined as a peak cortisol of <550 nmol/l after 250 μg of intramuscular cosyntropin (tetracosactide), according to locally derived normative data. ACTH reserve in the Dublin patient cohort was assessed by measuring the response of cortisol to either the ITT or the glucagon stimulation test (GST) pre‐operatively and 6 weeks postoperatively, as previously described 21. Testing was also performed annually in patients who underwent pituitary RT unless ACTH deficiency was already confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted these suggestions into routine surveillance programmes and recently published the results of an audit of the use of symptoms as predictors of hypopituitarism. We showed that symptoms of hypogonadism, such as menstrual dysfunction, erectile dysfunction or loss of libido are strongly predictive of hypopituitarism, but nonspecific symptoms such as weight loss and anergia are no more predictive than unselected screening in identifying pituitary hormone deficits (109).…”
Section: Chronic Hypopituitarismmentioning
confidence: 84%